Physiological, genetic, and molecular characterization of differential sensitivity of wheat (Triticum aestivum) to triketone herbicides - Sudhakar, Susee (Kansas State University, 2023)
Wheat (Triticum aestivum) is a major cash crop grown worldwide for food, feed, biofuel production, etc. Global wheat production is hindered by various biotic stresses, including weed infestation. Post-emergence (POST) application of herbicides is effective for weed management in wheat. Broadening the POST herbicide options is essential to combat the evolution of herbicide-resistant weeds. Triketone herbicides (mesotrione and tembotrione) belong to 4-hydroxyphenylpyruvate dioxygenase (HPPD) inhibitors (Group 27) and are widely used for broad-spectrum weed management in corn, which is naturally tolerant to triketones via cytochrome P450 (P450) enzyme-mediated metabolism; however not registered for use in wheat due to crop injury. The objectives of this dissertation were to a) characterize the response of a wide collection of wheat genotypes/lines to triketone herbicide treatment (Chapter 2), b) investigate the genetic basis of differential sensitivity of wheat to triketone herbicides (Chapter 3), and c) functional validation of genes responsible for wheat sensitivity to triketones via genetic engineering (Chapter 4). All experiments were conducted either in the greenhouse, controlled environmental growth chambers or in laboratory conditions. The results indicate that winter wheat genotypes, WW-1, WW-2, and Jagger were least sensitive to these herbicides compared to the most sensitive WW-24, mutant lines (J38 and J327), and spring wheat genotypes (Chapter 2). Importantly, high-performance liquid chromatography analyses suggested that WW-1, WW-2, and Jagger metabolize ~ 70 to 85% of ¹⁴C-tembotrione faster than the sensitive genotypes/lines. Further, the application of malathion (P450- inhibitor) followed by triketone herbicide treatment resulted in increased sensitivity of WW-1, WW-2, and Jagger, suggesting that similar to corn, P450 enzymes possibly are involved in metabolizing triketones in wheat as well (Chapter 2). In Chapter 3, the F1 and F2 progenies generated by direct and reciprocal crosses between WW-24 and WW-1 or WW-2 were evaluated for their response to different doses of mesotrione and tembotrione. The results indicate that the reduced sensitivity of WW-1 and WW-2 to these herbicides is a partially dominant, polygenic trait (Chapter 3). In Chapter 4, two genes of interest (GOI), i.e., wheat CYP81Q32-like (metabolic gene) and HPPD (the target site of these herbicides) were overexpressed in a sensitive spring wheat cultivar via genetic transformation. A total of 216 and 224 transgenic events were generated after bombarding with constructs containing the CYP81Q32-like or HPPD genes separately. The putative-transformed plants were screened for the presence of GOI. T₀ plants expressing the GOI were selected to generate T₁ plants. Upon phenotypic and genotypic analyses, a few T₁ plants were found to exhibit reduced sensitivity to mesotrione with high transcript expression of the GOI (Chapter 4). Taken together, the outcome of this dissertation provides valuable information that, a) rapid metabolism of triketone herbicides likely mediated by P450 activity, is a partially-dominant polygenic trait that bestows reduced sensitivity of WW-1 and WW-2 to these herbicides, and b) overexpression of CYP81Q32-like or HPPD genes can reduce the sensitivity of spring wheat to triketones. Importantly, these results also open up opportunities to develop triketone herbicide-resistant wheat cultivars, that can help broad-spectrum weed control without injury to the crop.
Keywords: Cytochrome P450; Mesotrione and Tembotrione; Overexpression of CYP81Q32-like; Reduced sensitivity of triketone herbicides in wheat; Metabolic resistance; Herbicide resistance